APPLICATION OF GRAPH THEORY AND WELCH-POWELL METHOD AT TRAFFIC LIGHT REGULATION - Diah Ayu Sulistiani; Chalawatul Ais; Aris Fanani (JUTI: Jurnal Ilmiah Teknologi Informasi, 2022)
Traffic lights are state-owned infrastructure facilities that are used to mark vehicles that must stop alternately from various directions. Traffic lights are often found at crossstreets, such as at the traffic lights on Jl. Margerejo with a long duration of red light and short green light. This study aims to obtain a traffic flow graph at the intersection of 4 Jalan Demak-Dupak Surabaya. Optimization of traffic light duration settings is very necessary on this street, because the long duration of the red light while the short duration of the green light causes the accumulation of vehicles at the intersection of Jalan Demak-Dupak Surabaya. In this study, the duration of the new traffic light was obtained, namely on Jl. Demak (North) red light 112.5 seconds and green light 37.5 seconds. For Jl. Dupak red light 84 seconds and green light 28 seconds. Jl. Demak (South) red light for 135 seconds and green light for 45 seconds. And for the axle Jl. Surabaya-Gresik red light for 84 seconds and green light for 28 seconds. The level of effectiveness of the green light is obtained by a value of 21.77% and the level of effectiveness of the red light is 6.62%.